Experimental investigations on feasibility of corn cob as a potential feed stalk for biochar production - Wakudkar, Harsha; Jain, Sudhir; Panwar, N L; Salvi, B L; Singh, P K (Journal of Postharvest Technology, 2023)
Burning of agricultural waste is nowadays practiced predominantly to eradicate the unutilized waste material. It pollutes the atmosphere with massive amounts of particulate and gaseous contaminants. Corn cob is one of such material remains unutilized, that can be used for potential applications. Biochar is black colored porous carbon material obtained by slow pyrolysis in absence of oxygen. It has many applications such as soil ameliorant, composting, pharmaceutical and industrial usage. This paper is compiled with the aim to check feasibility of corn cob as a feedstock for biochar production. The characteristics of corn cob such as elemental composition, proximate analysis, and thermo-gravimetric analysis have been presented in this article. The results revealed good amount of carbon in biomass i.e., 45 % which is good for biochar production. The low content of nitrogen and sulphur suggests environmentally friendly utilization of biomass. This conversion of corn cob into biochar offers advantages of utilization of waste residues for holistic purpose.